2023
DOI: 10.1038/s41598-023-44254-9
|View full text |Cite
|
Sign up to set email alerts
|

Spin effects on transport and zero-bias anomaly in a hybrid Majorana wire-quantum dot system

Alexandre Huguet,
Kacper Wrześniewski,
Ireneusz Weymann

Abstract: We examine the impact of spin effects on the nonequilibrium transport properties of a nanowire hosting Majorana zero-energy modes at its ends, coupled to a quantum dot junction with ferromagnetic leads. Using the real-time diagrammatic technique, we determine the current, differential conductance and current cross-correlations in the nonlinear response regime. We also explore transport in different magnetic configurations of the system, which can be quantified by the tunnel magnetoresistance. We show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…For , the current does not flow through the system, however, the differential conductance clearly reveals a strong zero-bias peak associated with the Majorana modes leaking into the quantum dots. We note that the basic dependencies of the zero-bias anomaly on various model parameters have recently been studied in a hybrid Majorana system with one quantum dot coupled to ferromagnetic leads 53 . However, in the case of the double quantum dot-Majorana device considered here, we have the opportunity to study the behavior of a non-local zero-bias anomaly revealed in magnetotransport properties, which will be comprehensively discussed later on.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For , the current does not flow through the system, however, the differential conductance clearly reveals a strong zero-bias peak associated with the Majorana modes leaking into the quantum dots. We note that the basic dependencies of the zero-bias anomaly on various model parameters have recently been studied in a hybrid Majorana system with one quantum dot coupled to ferromagnetic leads 53 . However, in the case of the double quantum dot-Majorana device considered here, we have the opportunity to study the behavior of a non-local zero-bias anomaly revealed in magnetotransport properties, which will be comprehensively discussed later on.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of the leads’ spin polarization, the strength of coupling to the Majorana wire, and the overlap between the two edges of the nanowire have all been previously analyzed for systems consisting of a single quantum dot 53 . Those results are quantitatively relevant to the system under consideration in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations